اقتراح أنموذج لمعايير تصميم البرامج التدريبية وتنفيذه على منصة مودل ( Moodle ) وقياس فاعليته في تطوير مهارات المتدربين وأدائهم بوزارة التربية والتعليم في سلطنة عمان - حضرمي، شيخة حمد سليمان
The current study aimed to suggest standards for designing and implementing training programs implemented on the Moodle platform by identifying the international models and studies and the experiences of Gulf and international institutions in this field. This was followed by measuring the effectiveness of training programs designed in line with the proposed standards on the performance and skills of trainees of the Ministry of Education in the Sultanate of Oman. Finally, the extent to which the training institution has applied the proposed standards in designing and implementing training programs in line with the proposed standards was measured from the point of view of the training programs trainers. The strengths and weaknesses of the proposed model were then isolated, coming up with the final model as the product of the current study. The study population consisted of employees of the Ministry of Education in the Sultanate of Oman who benefited from the e-training programs implemented on the e-learning platform (LMS) represented by the Moodle platform. The study sample included (346) trainees. The researcher used the qualitative and quantitative approach based on interview, pre and posttests, and questionnaire as tools for the study. The study reached a number of results, the most important of which are: There is positive effectiveness of the proposed standards on developing the skills of trainees, as it was found that departments are satisfied with the training programs designed in line with the proposed standards, given the role played by the standards in improving the training programs provided on the Moodle platform at the Ministry of Education. The study proposed several recommendations, the most important of which are: The necessity to follow the proposed model when designing and implementing training programs on the e-learning platform of the Omani Ministry of Education. Finally, the study recommended that there be frameworks that regulate ethical laws related to various aspects of the training process, especially with regard to the Intellectual property aspect.